Melhoria no desempenho lumínico e energético de edifícios com prateleiras de luz - Alves Netto, Ary Rodrigues (2015)
Energy consumption due to the economic development of countries impacts directly on the environment and causes investments in the power generation conventional or alternative infrastructure. Lighting systems are responsible for much of the energy consumed in buildings and in urban areas, demanding action to improve energy efficiency. The use of natural light is one of the factors that contribute most to obtain energy savings in lighting on buildings. Using natural lighting in improving the lightining performance of the building will be through the analysis of light shelves behavior, redirecting both, direct sunlight and widespread in the celestial dome for indoor environments. To analyze were made computational models of a building on UFSCar and other in IPT, using TropLux software. The simulation results indicate that the use of redirector device of natural light in buildings improves illuminance levels and their distribution in the sites studied. With the simulations results, was estimated how much can be saved in electricity that would be spent floodlit by identifying the level of energy efficiency of the studied system.